Great Theorists of Central European Integration in Hungary - Pallai, Laszlo (Great Theorists of Central European Integration, 2023)
In Hungary, too, the idea of Central European cooperation has constantly been on the agenda. The reasons for this interest are similar to those in Austria: with the emergence of the idea of the nation-state, existing political structures steadily lost their stability. Integrationist ideas have always been an alternative to the current power relations. Although these plans have remained present in the Hungarian political world, they have never had the chance to be realised: they have received minimal support from the great powers and society, and the peoples and governments of the region have not acted as partners for real cooperation. Miklós Wesselényi was one of the first to formulate a programme for the transformation of the Habsburg Empire and the need for reconciliation with various nationalities. Kossuth was the most prestigious figure of the Hungarian emigration after 1849, which is why the plan for the Danubian Confederation is mainly associated with him, though his fellow politicians formulated similar ideas. Oszkár Jászi’s plan for the reorganisation of the Monarchy was born too late, as its fate had been decided prior to its publication in 1918. Between the two World Wars, Gusztáv Gratz and Elemér Hantos were the most active organisers, publicists, and experts in the field of Central European cooperation.KEYWORDS:Hungarian history, history of ideas, history of politics, history of integration, history of theReform Era, history of dualism, history of Hungarian emigration, history of the dissolution ofthe Monarchy, revolutions of 1918-19, Hungary between the two World Wars, Central Europeanplans, Pan-European Movement, Miklós Wesselényi, Lajos Kossuth, Oszkár Jászi, Gusztáv Gratz,Elemér Hantos.